ارضِ مقدس’ فلسطین‘الہامی مذاہب کے تناظرمیں؛ایک تجزیاتی مطالعہ: The Sacred Land of Palestine in the context of divine religions: an Analytical study - Aziz , Dr. Asma; Fatima, Noor (Al-Amīr Research Journal for Islamic Studies, 2023)
The land of Palestine carries importance in every Semitic religion. This land has been called “Sacred Land” because of its importance in three Abrahamic religions, Judaism, Christianity and Islam. Its significance and holiness to inspired religion derives from its strong association with Prophet Abraham, David, Solomon and Jesus. In addition to that, thousands of Prophets belong to this Holy land; their graves make this land sacred for the believers. The holy perspective manifested in teachings of all three religions is the only way to study history of this sacred land. Keywords: Sacred Land, Palestine, Masjid al Aqsa, Semitic religion, historical facts.